Modernization of Applicated Arts of Folk Crafts - Qurbonov Bahodir Ernazarovich (International Journal on Integrated Education, 2022)
The stages of development of Uzbek folk handicrafts and art design, methodological bases, main stages of historical development, directions of Uzbek national handicrafts, materials used in folk handicrafts, equipment and modern approaches and recommendations for its use are described. Great attention is paid to the applied arts of folk handicrafts, and in order to develop the centuries-old traditions of handicrafts, various products, various models are drawn and models are made. Students are developing their talents and creativity by carefully studying wood materials, making airplane models, car models, and various wheelchairs. According to the art of carpet weaving, carpets are woven on the basis of various designs, in the form of images of buildings and structures. Students will have a variety of ideas, thoughts, and vivid imaginations to create innovations while enjoying the creative performances they perform.